ANALISIS YURIDIS PENYELESAIAN PEMUTUSAN HUBUNGAN KERJA MASAL PADA PEKERJA PERUSAHAAN RAMBUT - Pangestu, Gema Ramadhanu Ridho Ing; Wardani, Susilo (Collegium Studiosum Journal, 2025)
Mass termination of employment (PHK massal) is a critical issue in the labor sector, as it directly impacts job loss and income reduction. Purbalingga Regency, known as a hub for the wig and false eyelash industry, has significantly contributed to employment absorption and poverty reduction. However, mass terminations of employment still frequently occur, causing numerous challenges, especially for affected workers. This study aims to examine the legal resolution mechanisms of mass termination of employment in hair companies in Purbalingga Regency and to identify the challenges faced by workers affected by such terminations. The research employs both normative and empirical juridical approaches. The normative juridical approach involves a review of relevant legislation and legal doctrines, while the empirical juridical approach is conducted through interviews with relevant parties, particularly the Purbalingga Regency Department of Manpower and labor unions. The findings reveal that the Purbalingga Department of Manpower facilitates the resolution of mass terminations in hair companies by adhering to legal procedures through bipartite negotiations, mediation, and proceedings at the Industrial Relations Court in accordance with Law Number 13 of 2003 on Manpower. Nonetheless, several obstacles persist, including weak financial conditions of companies, workers limited understanding of legal mechanisms, and high levels of worker poverty. Therefore, collaboration among local governments, companies, and labor unions is necessary to ensure legal protection and justice for workers.